Essential functions of RNA helicase Vasa in maintaining germline stem cells and piRNA-guided Stellate silencing in Drosophila spermatogenesis - Adashev, Vladimir E.; Kotov, Alexei A.; Bazylev, Sergei S.; Kombarov, Ilia A.; Olenkina, Oxana M.; Shatskikh, Aleksei S.; Olenina, Ludmila V. (Frontiers in Cell and Developmental Biology, 2024)
DEAD-box RNA helicase Vasa is required for gonad development and fertility in multiple animals. Vasa is implicated in many crucial aspects of Drosophila oogenesis, including translation regulation, primordial germ cell specification, piRNA silencing of transposable elements, and maintenance of germline stem cells (GSCs). However, data about Vasa functions in Drosophila spermatogenesis remain controversial. Here we showed that loss-of-function vasa mutations led to failures of GSC maintenance in the testes, a severe loss of total germ cell content, and a cessation of male fertility over time. Defects in GSC maintenance in vasa mutant testes were not associated with an increasing frequency of programmed cell death, indicating that a premature loss of GSCs occurred via entering differentiation. We found that Vasa is implicated in the positive regulation of rhino expression both in the testes and ovaries. The introduction of a transgene copy of rhino, encoding a nuclear component of piRNA pathway machinery, in vasa mutant background allowed us to restore premeiotic stages of spermatogenesis, including the maintenance of GSCs and the development of spermatogonia and spermatocytes. However, piRNA-guided repression of Stellate genes in spermatocytes of vasa mutant testes with additional rhino copy was not restored, and male fertility was disrupted. Our study uncovered a novel mechanistic link involving Vasa and Rhino in a regulatory network that mediates GSC maintenance but is dispensable for the perfect biogenesis of Su(Ste) piRNAs in testes. Thus, we have shown that Vasa functions in spermatogenesis are essential at two distinct developmental stages: in GSCs for their maintenance and in spermatocytes for piRNA-mediated silencing of Stellate genes.